Aplikasi Kamus ViKA sebagai Visualitator Kosakata Bahasa Arab untuk Pembelajar Pemula - Lia Sunarti; Ernawati Ernawati; Marja’i Affan (LISANIA: Journal of Arabic Education and Literature, 2017)
This research aims to produce a digital dictionary ViKA (Visualitation by Creation and Action) as media for for beginner learners to understand the meaning of Arabic vocabulary according the morphology (Creation) and syntax (Action). This Research and Development uses quantitative data for the analysis with the independent variables "ViKA Dictionary" and the dependent variable “the ineffectiveness of existing dictionaries and the effectiveness of ViKA dictionary. ViKA Dictionary is tested to 50 of 1st semester students of Arabic Education at State  Institute for Islamic Studies Salatiga, with the  data is obtained through Pre-ViKA and Post-ViKA questionnaires and interviews. Signification test of the data is done by two-tailed test to accept an alternative hypothesis "That students of Arabic Education 1st Semester are beginner learners and existing dictionaries give understanding of detail meaning of Arabic vocabulary yet and ViKA dictionary is effective for use", or reject the null hypothesis "That 1st semester students of Arabic Education 1st are not beginner learners and existing dictionaries give understanding of detail meaning of Arabic vocabulary and ViKA dictionary is ineffective for use ". The result of signification test according to the rules decision of  two-tailed test is whether the H1 is accepted and H0 is rejected. So "ViKA Dictionary is effective being used by beginner Arabic learners".